The Influence of Information Technology and Computer Skills on Accounting Information Systems - Nelyumna Rizal; Amelia Oktrivina; Razi Muhammad (LPMP Imperium, 2021)
This study examines the effect of information technology and computer skills on accounting information systems at PT Bumi Jawa Kayana. The method used in this research is the descriptive and correlation method. The data used in this research is primary data from distributing questionnaires to 32 respondents. The sample selection used the purposive sampling technique. The data analysis technique used multiple regression statistical techniques, which were processed using SPSS 20.0 software. The results prove that the information technology variable significantly affects the accounting information system at PT Bumi Jawa Kayana. Likewise, the variable of computer skills has a significant effect on the accounting information system at PT Bumi Jawa Kayana. The coefficient of determination (Adjusted R Square) is 0.631 or 63.1%. Accounting Information Systems can be explained by the Information Technology and Computer Skills variables. At the same time, the remaining 36.9% of Accounting Information System variables can be explained by other variables not examined in this study.